Advancing Early Childhood Development and Prevention Programs: A Pan‐Canadian Knowledge Transfer Initiative for Better Beginnings, Better Futures. Issue 3 (14th August 2018) - Worton, S. Kathleen; Nelson, Geoffrey; Loomis, Colleen; Mark Pancer, S.; Hayward, Karen; Peters, Ray DeV.
Abstract : Better Beginnings, Better Futures is an evidence‐based early childhood initiative that promotes the healthy development of children and families in economically disadvantaged communities. The Better Beginnings model involves the development of community‐driven programs through resident involvement that are integrated with existing services, universally accessible to all children and families in a community, focused on prevention, and ecological in nature. In this paper, we describe a pan‐Canadian knowledge transfer strategy involving attendance at workshops designed to build the capacity of participants to develop Better Beginnings initiatives in their own communities, and the impacts of the workshops on participants. Process evaluation data were obtained from participants in each Canadian province and territory immediately following the workshops ( k = 12, N = 271). In addition, a smaller sample ( n = 54) completed a follow‐up telephone interview 3 months later. All components of the knowledge transfer strategy were well‐received and rated highly by participants. Workshop participants indicated increased knowledge of the Better Beginnings model and high levels of satisfaction with the workshop. In the follow‐up evaluation, participants indicated strong intentions to use the information they had learned about Better Beginnings to advance the well‐being of children and families in their community. We discuss the lessons learned from the knowledge transfer initiative and provide recommendations for advancing knowledge transfer of programs for children and families in context.